The Effects Of Dry And Chilled Air On Tool Wear Behavior During Face Milling Of Inconel 718 - Kasim, Mohd Shahir; Mohd Shahrim, Mohammad Shah All Hafiz; W. Mohamad, W Noor Fatihah; Mohd Zainurin, Nurul Shafiqah; Othman, Intan Sharhida; Raja Abdullah, Raja Izamshah; Mat Harttar, Maziati Akmal; Mohamed, S.B.; Nawi, M.A.M. (Malaysian Tribology Society (MYTRIBOS), 2019)
Tool wear is one of the important criteria during the cutting process. It is mostly caused by the machining parameters, namely; cutting speed, feed rate, depth of cut, cooling condition, etc. This paper presents the behavior of cutting tool during dry and chilled air condition of face mill with the cutting speed of 20 to 40 m/min, the feed rate of 0.1 to 0.2 mm/tooth and axial depth of 0.1 mm. The analysis of variance (ANOVA) is applied to identify the significance of these factors effect on tool performance, later the mathematical model for the tool life prediction was developed. The investigation revealed that the cutting speed, feed rate dominating wear rate whilst the chilled air found to be marginally significant. Finally, the optimum condition for machining parameter for greater tool life can be obtained by the combination cutting speed of 20 m/min, the feed rate of 0.1 mm/tooth under chilled air condition. Implementation of chilled air contributed 7% improvement with 45 min compared to a dry condition. The study exhibited the round type insert of dry face milling is more prone to rapid flank wear than chilled air with no BUE appearance on the tool cutting edge.